Chapter Caterina Colombini, o della cugina sedotta. Una 'ricostruzione' della figura di Caterina attraverso i testi - Zangari, Mattia (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
In this essay the author demonstrates that it is possible to "reconstruct" the figure of Caterina Colombini (1340?-1387) - Giovanni Colombini's cousin - through a group of texts: the hagiography of Caterina, the letters sent to her by Giovanni Colombini and, finally, Giovanni's biography written by Feo Belcari. The author divides his text into four parts: the first part analyzes the content of Caterina's hagiography; the second examines the linguistic form of the hagiographic text; in the third, the author analyzes the latent meaning of the window, a symbolic place where Giovanni and Caterina converse on divine topics; in the last part, to conclude, the teachings that Giovanni gives to Catherine and her spiritual daughters - the Gesuate - are analyzed.